Precarious Work in The Indonesian Labour Law System: A Study of Freelance Workers - Ramadhani, Salmaa Al Zahra; Kristanto, Novi Eka (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The development of flexible working patterns, particularly for freelance workers, is a phenomenon that is inseparable from the transformation of the modern labour market and the digital economy. However, Indonesia's labour law system is still oriented towards conventional employment relationships, so it is not yet able to provide adequate legal certainty and protection for freelance workers. This study aims to analyse the legal position of freelance workers in Indonesia's labour law system and the forms of legal protection for the fulfilment of their normative rights. The research method used is normative legal research with a legislative, conceptual, and limited comparative approach to international labour standards. The results of the study show that the absence of explicit regulations regarding freelance workers creates a legal grey area that results in weak protection of their rights to wages, social security, and occupational welfare. This condition places freelance workers in the category of precarious work, which is socially and economically vulnerable. This study emphasises the urgency of updating labour regulations to be more inclusive and adaptive, using the International Labour Organisation (ILO) standards on non-standard employment as a normative reference, in order to realise a fair and sustainable labour system.